2018
DOI: 10.3389/fendo.2018.00130
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Thyroid Hormones, Thyroid Antibodies, and Cardiometabolic Factors in Non-Obese Individuals With Normal Thyroid Function

Abstract: BackgroundHypothyroidism is an important risk factor for cardiovascular diseases, and autoimmune thyroiditis (AIT) is the leading cause of hypothyroidism. Recent studies showed that even AIT patients with euthyroidism still had an increased number of early atherosclerotic lesions. However, the precise mechanism is not yet known. This study aimed to investigate the association of thyroid function, thyroid autoimmunity, and cardiometabolic risk factors in non-obese AIT patients with euthyroidism.MethodsA total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 40 publications
(48 reference statements)
2
46
0
Order By: Relevance
“…It is also the most sensitive marker for Hashimoto's thyroiditis and associate with the degree of infiltration by lymphocytes. TPOAb is able to induce and activate the complement system and exert the cellular cytotoxicity [17]. In the previous studies, TPOAb levels were positively related to the C reactive protein and multiple pro-inflammatory cytokines such as TNF-α, interleukin-6, and interferon-γ [22].…”
Section: Correlation Between Rhi and Other Parametersmentioning
confidence: 95%
See 1 more Smart Citation
“…It is also the most sensitive marker for Hashimoto's thyroiditis and associate with the degree of infiltration by lymphocytes. TPOAb is able to induce and activate the complement system and exert the cellular cytotoxicity [17]. In the previous studies, TPOAb levels were positively related to the C reactive protein and multiple pro-inflammatory cytokines such as TNF-α, interleukin-6, and interferon-γ [22].…”
Section: Correlation Between Rhi and Other Parametersmentioning
confidence: 95%
“…In the previous studies, Hashimoto's patients had increased C reactive protein, interleukin 6, interleukin 1β, and tumor necrosis factor α levels. It is suggested that Hashimoto's patients were in the state of chronic inflammation [16,17]. In addition, Hashimoto's patients also had higher levels of soluble intercellular adhesion molecule 1 (sICAM-1) and soluble vascular cell adhesion molecule-1 (sVCAM-1) although they were in the euthyroidism states [18].…”
Section: Correlation Between Rhi and Other Parametersmentioning
confidence: 99%
“…The scientific research on the relevance of low-normal thyroid function on components of the metabolic syndrome (MS) shows that the state is significantly associated with all components of MS (34). Several studies in obese and also in non-obese individuals, with thyroid function at normal range, presented the results of association between elevated thyroid antibodies with insulin resistance and hsCRP (16,35). Low-normal thyroid function may be implicated into atherosclerosis development via connections with insulin resistance and metabolic syndrome (36).…”
Section: Discussionmentioning
confidence: 99%
“…Detection of TPOAbs during pregnancy can predict the development of post-partum thyroiditis [49]. Increased interest has been focused on the association between thyroid function and metabolic disorders in euthyroid individuals [55,56]. For example, Liu et al have recently shown that TPOAbs level is associated with cardiometabolic risk factors in non-obese euthyroid individuals [56].…”
Section: Clinical Utility Of Tpoabs Testingmentioning
confidence: 99%
“…Increased interest has been focused on the association between thyroid function and metabolic disorders in euthyroid individuals [55,56]. For example, Liu et al have recently shown that TPOAbs level is associated with cardiometabolic risk factors in non-obese euthyroid individuals [56]. Another widely discussed issue is the connection between thyroid antibodies and cancer [57][58][59].…”
Section: Clinical Utility Of Tpoabs Testingmentioning
confidence: 99%